Predicción estacional para ASO de eventos extremos y días con precipitación sobre las vertientes Pacífico y Caribe de América Central, utilizando análisis de correlación canónica - Maldonado Mora, Tito José (2012)
Models were generated based on Canonical Correlation Analysis for prediction of extreme precipitation events during August-September-October (ASO), using as predictor the Sea Surface Temperature (SST) due to the hydrological response of the SST anomalies over the isthmus, and as predictant, the accumulated monthly rainfall, days with precipitation, the percentage of days exceeding the 80th percentile (extreme wet) and the percentage of days that do not exceed the 10th percentile (dry extreme). It was found that using the July SST properly relate ENOS and AMO events with the prediction of precipitation extremes for ASO.